Formative Assessment Using Direct Behavior Ratings: Evaluating Intervention Effects of Daily Behavior Report Cards. (December 2017) - Sims, Wesley A.; Riley-Tillman, Chris; Cohen, Daniel R.
This study examined the treatment sensitivity of Direct Behavior Rating–Single Item Scales (DBR-SIS) in response to an evidence-based intervention delivered in a single-case, multiple-baseline design. DBR-SIS was used as a formative assessment in conjunction with a frequently used intervention in schools, a Daily Behavior Report Card (DRC). The intervention and concurrent assessment were conducted by five teachers in a rural Midwestern elementary school with five male students displaying mild to moderate behavioral challenges in the classroom. Study findings indicated DBR-SIS displays appropriate treatment sensitivity following intervention implementation. Agreement in the documentation of response and nonresponse to intervention implementation between DBR-SIS and systematic direct observation (SDO) data was evident across visual and empirical analyses. In addition, through a multiple-baseline design, this study documented negligible to no change in student behavior following implementation of a DRC in an applied classroom setting. These findings support previous calls for continued examination of the forms and components of DRC employed in schools. Finally, the study found educators rated the use of a combined DRC intervention and progress monitoring with DBR-SIS as favorable.